2008
DOI: 10.1101/gad.1668708
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of differentiation 4 drives brain tumor-initiating cell genesis through cyclin E and notch signaling

Abstract: Cellular origins and genetic factors governing the genesis and maintenance of glioblastomas (GBM) are not well understood. Here, we report a pathogenetic role of the developmental regulator Id4 (inhibitor of differentiation 4) in GBM. In primary murine Ink4a/Arf −/− astrocytes, and human glioma cells, we provide evidence that enforced Id4 can drive malignant transformation by stimulating increased cyclin E to produce a hyperproliferative profile and by increased Jagged1 expression with Notch1 activation to dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
111
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 25 publications
2
111
0
2
Order By: Relevance
“…Expanding on past work (AndresBarquin et al, 1997; Vandeputte et al, 2002;Jeon et al, 2008), we found ID4 elevated in glioblastoma multiforme (GBM), a highly aggressive and well-vascularized brain tumor that is refractory to existing therapies (Kleihues and Cavenee, 1997). The difficulties in treating this tumor led us to investigate the potential function of ID4 in the pathogenesis of glioblastoma.…”
Section: Introductionmentioning
confidence: 51%
See 3 more Smart Citations
“…Expanding on past work (AndresBarquin et al, 1997; Vandeputte et al, 2002;Jeon et al, 2008), we found ID4 elevated in glioblastoma multiforme (GBM), a highly aggressive and well-vascularized brain tumor that is refractory to existing therapies (Kleihues and Cavenee, 1997). The difficulties in treating this tumor led us to investigate the potential function of ID4 in the pathogenesis of glioblastoma.…”
Section: Introductionmentioning
confidence: 51%
“…ID family members including ID1, ID2, and ID3 have identified functions in tumor progression, including angiogenesis, invasion, and metastasis (Lyden et al, 1999;Benezra, 2001;Benezra et al, 2001;Folkman, 2002;Ruzinova and Benezra, 2003;, and in other circumstances ID1 and ID2 may function as tumor suppressors in rodents (Itahana et al, 2003;Sikder et al, 2003;Russell et al, 2004). The function of ID4 in tumorigenesis is similarly complex (Beger et al, 2001;Bellido et al, 2003;Chan et al, 2003;Shan et al, 2003;Umetani et al, 2004Umetani et al, , 2005 Jeon et al, 2008). ID4 seems to function as a tumor suppressor in a variety of cancers (Chan et al, 2003;Umetani et al, 2004Umetani et al, , 2005Yu et al, 2005) and is downregulated by promoter hypermethylation in several tumor types (Chan et al, 2003;Umetani et al, 2004Umetani et al, , 2005Yu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notch signaling is a critical developmental pathway that controls neural stem cell fate and suppresses radial glia differentiation (Ehebauer et al, 2006). The notch signaling pathway is constitutively active in many high-grade gliomas and has been associated with progression of gliomas (Hulleman et al, 2009;Jeon et al, 2008;Shih and Holland, 2006;Zhang et al, 2008). Notch signaling from endothelial cells to hematopoetic stem cells (HSC) via expression of Notch ligands has been shown to drive the self-renewal characteristics and in vivo repopulation of long-term HSCs that lie adjacent to the vasculature (Butler et al, 2010).…”
Section: Brain Tumor-cell Endothelial-cell Signalingmentioning
confidence: 99%